Toleransi Beragama: Analisis Wacana Kritis Fairclough Pada Program LOGIN Episode 30 Season 2 - Delahoya, Samuel (LP2M UIN Sunan Kalijaga, 2024)
This study is based on the reality of religious diversity in Indonesia which is plural and diverse. There are many religions, both conventional and traditional religions or commonly referred to as tribal religions, such as Kaharingan, Marapu, Parmalim, Kejawen. Therefore, Indonesia is rich in diversity, especially in the dimension of religious life. The development of technology is very rapid in the current era, both on a global and national scale, one of which is in Indonesia. YouTube is a media that has experienced very rapid development. This media is in demand by its activists by uploading videos on channels for certain purposes, one of which is LOGIN on Deddy Corbuzier's Channel. The purpose of this study is to see the discourse and ideology in the videos uploaded on the LOGIN program, especially in episode 30 season 2. The method in this study is qualitative with two methods, namely Fairclough's critical discourse analysis and descriptive analysis. This study begins by presenting the theory related to interfaith dialogue from Knitter and Kung, then analyzing the LOGIN video episode 30 season 2 and 3 other videos: episodes 1 and 30 season 1, and episode 1 season 2. The results of the discourse analysis want to see the discourse of tolerance that is born through harmonious and comedic religious dialogue from each religious figure in the LOGIN program video.[Penelitian ini berangkat dari realitas keberagaman agama di Indonesia yang plural dan majemuk. Banyak sekali agama-agama, baik dari agama yang konvensional maupun agama yang tradisional atau biasa disebut sebagai agama suku, seperti kaharingan, marapu, parmalim, kejawen. Oleh karena itu, Indonesia kaya akan keberagaman, khususnya dalam dimensi kehidupan keagamaan. Perkembangan teknologi sangat pesat di era sekarang, baik dalam skala global maupun negara, salah satunya di Indonesia. YouTube menjadi media yang mengalami perkembangan sangat pesat. Media ini diminati oleh para pegiatnya dengan mengunggah video di channel untuk tujuan tertentu, salah satunya adalah LOGIN di Channel Deddy Corbuzier. Tujuan penelitian ini untuk melihat wacana dan ideologi pada video yang diunggah di program LOGIN, khususnya di episode 30 season 2. Metode dalam penelitian ini adalah kualitatif dengan dua metode yakni analisis wacana kritis Fairclough dan analisis deskriptif. Penelitian ini dimulai dengan memaparkan teori terkait dialog antar agama dari Knitter dan Kung, kemudian menganalisis video LOGIN episode 30 season 2 dan 3 video lainnya: episode 1 dan 30 season 1, serta episode 1 season 2. Hasil dari analisis wacana tersebut ingin melihat wacana toleransi yang lahir melalui dialog agama yang harmoni dan bernuansa komedi dari setiap tokoh-tokoh agama di dalam video program LOGIN.]